Targeting CD93 on monocytes revitalizes antitumor immunity by enhancing the function and infiltration of CD8+ T cells - Yan Wu; Da Jiang; Xing-Chen Liu; Yong-Hao Ruan; Limin Zheng; Aiqi Huang; Bai-Xi Zhu; Jiangling Gong (Journal for ImmunoTherapy of Cancer)
Background Limited activation and infiltration of CD8+ T cells are major challenges facing T cell-based immunotherapy for most solid tumors, of which the mechanism is multilayered and not yet fully understood.Methods Levels of CD93 expression on monocytes from paired non-tumor, peritumor and tumor tissues of human hepatocellular carcinoma (HCC) were evaluated. The underlying mechanisms mediating effects of CD93+ monocytes on the inhibition and tumor exclusion of CD8+ T cells were studied through both in vitro and in vivo experiments.Results In this study, we found that monocytes in the peritumoral tissues of HCC significantly increased levels of CD93 expression, and these CD93+ monocytes collocated with CD8+ T cells, whose density was much higher in peritumor than intratumor areas. In vitro experiments showed that glycolytic switch mediated tumor-induced CD93 upregulation in monocytes via the Erk signaling pathway. CD93 on the one hand could enhance PD-L1 expression through the AKT-GSK3β axis, while on the other hand inducing monocytes to produce versican, a type of matrix component which interacted with hyaluronan and collagens to inhibit CD8+ T cell migration. Consistently, levels of CD93+ monocytes positively correlated with the density of peritumoral CD8+ T cells while negatively correlated with that of intratumoral CD8+ T cells. Targeting CD93 on monocytes not only increased the infiltration and activation of CD8+ T cells but also enhanced tumor sensitivity to anti-PD-1 treatment in mice in vivo.Conclusion This study identified an important mechanism contributing to the activation and limited infiltration of CD8+ T cells in solid tumors, and CD93+ monocytes might represent a plausible immunotherapeutic target for the treatment of HCC.